Kontribusi Kerja Sama Tim terhadap Efektivitas Organisasi : Systematic Literature Review - Ariska Amelia Velanda; Nindy Syera Fortuna; Christina Angel Purnomo; Hastina Ramadhani; Mada Aditia Wardhana (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
This study aims to systematically review the literature related to teamwork in the context of formal organizations, with a focus on concept mapping, identification of key factors, and remaining research gaps. The method used is Systematic Literature Review (SLR) by analyzing 797 articles published in 2021-2025. The selection process was rigorous using inclusion and exclusion criteria, followed by thematic coding to identify key patterns. The analysis showed that effective communication, participative leadership, and psychological safety are the main factors that shape solid teamwork and positively impact employee performance and job satisfaction. However, there were a number of organizational contexts where teamwork did not contribute significantly, indicating the need for attention to contextual factors, organizational culture and psychosocial dynamics. This study makes theoretical and practical contributions to designing evidence-based organizational interventions to sustainably improve teamwork effectiveness.